Gene therapy for cystic fibrosis: Challenges and prospects - Sui, Hongshu; Xu, Xinghua; Su, Yanping; Gong, Zhaoqing; Yao, Minhua; Liu, Xiaocui; Zhang, Ting; Jiang, Ziyao; Bai, Tianhao; Wang, Junzuo; Zhang, Jingjun; Xu, Changlong; et al. (Frontiers in Pharmacology, 2022)
Cystic fibrosis (CF) is a life-threatening autosomal-recessive disease caused by mutations in a single gene encoding cystic fibrosis transmembrane conductance regulator (CFTR). CF effects multiple organs, and lung disease is the primary cause of mortality. The median age at death from CF is in the early forties. CF was one of the first diseases to be considered for gene therapy, and efforts focused on treating CF lung disease began shortly after the CFTR gene was identified in 1989. However, despite the quickly established proof-of-concept for CFTR gene transfer in vitro and in clinical trials in 1990s, to date, 36 CF gene therapy clinical trials involving ∼600 patients with CF have yet to achieve their desired outcomes. The long journey to pursue gene therapy as a cure for CF encountered more difficulties than originally anticipated, but immense progress has been made in the past decade in the developments of next generation airway transduction viral vectors and CF animal models that reproduced human CF disease phenotypes. In this review, we look back at the history for the lessons learned from previous clinical trials and summarize the recent advances in the research for CF gene therapy, including the emerging CRISPR-based gene editing strategies. We also discuss the airway transduction vectors, large animal CF models, the complexity of CF pathogenesis and heterogeneity of CFTR expression in airway epithelium, which are the major challenges to the implementation of a successful CF gene therapy, and highlight the future opportunities and prospects.